STANDARISASI DAN EFEK ANTIKONVULSI EKSTRAK ETANOL DAUN UBI JALAR PADA MENCIT PUTIH JANTAN - Erjon Nazir (Jurnal Penelitian Farmasi Indonesia, 2016)
ABSTRACT Sweet potato (Ipomoea batatas (L.) lam) leaf has been reported contain flavonoids that can modulate GABAa. It a role in providing anticonvulsant effects. The standarization of extract and anticonvulsant effect of ethanol extract of sweet potato (Ipomoea batatas (L.) lam) leaves with striknin induced seizures in mice at dose levels 200, 400, 800 mg / kgbw an diazepam as comparison has been conducted. The test involved spesific and non spesific parameters according to standarisation method from legitimate literature. Result showed that on extract had a thick form, green-blackish, spesific smell, bitter taste, content of compounds solube in water 57,24%, solube in ethanol 40,11%, water content of 5,11%, ash content 7,84%, ash content solube in acid 5,48%, ash content unsolube in acid 0,72%, and thin layer chromatography profile of extract showed flavonoids, fenols, steroids, and alkaloids. Parameters of observation of anticonvulsion effect used were onset of seizure, recovery time, and death time. Result showed a diference significant, extract of sweet potato (Ipomoea batatas (L.) lam) significantly delayed the onset time of convulsions (314,8±16,27 seconds) and death time (323,8±8,10 seconds) in doses 200 mg/kgbw. The highest anticonvulsant effect was showe by doses 800 mg / kgbw, with onset time of convulsions (555.6 ± 11.63 seconds) and recovery time (83.4 ± 4.66 seconds). Result showed that increasing doses extract of sweet potato (Ipomoea batatas (L.) lam) leaves has a positive correlation to prolong onset time, accelerate the recovery time, and delay the death time. So that it can be concluded that increasing the dose can magnify the effects of anticonvulsant